Harmonization of Indonesia-Malaysia border communities based on socio-culture - Azwar, Idham; Novianty, Fety; Yuliananingsih, Yulianingsih (Universitas Negeri Yogyakarta, 2024)
Harmonizing the border society between Indonesia and Malaysia based on their socio-cultural similarities presented an exciting exploration into the social and cultural dynamics that formed the relationship between these neighboring countries. This study explored the complex interactions of traditions, faiths, and practices that fostered cross-border unity and cooperation and highlighted the socio-cultural foundations that bind these communities together. The research was conducted in the border area between Indonesia and Malaysia, especially at Aruk Village, Sajingan Besar District, Sambas Regency. The method used in this research is phenomenology with the qualitative approach. The research findings indicated that the community at Aruk Village collectively managed the forests and natural resources. There were several cultural similarities among the Dayak Ethnic, Bidayu Sub-ethnic, and Melayu Ethnic who stayed in the Aruk Village area. This research highlighted local ideologies' role in strengthening social togetherness. Local wisdom, a binding force, was found to contribute significantly to the prosperity of the society, instilling a sense of optimism about the future of these communities. The harmonization of the border society between Indonesia and Malaysia showed the cognation of those residing in Aruk Village, Indonesia, with those residing in Serawak, Malaysia.